Headmaster’s Transformational Leadership and Teacher’s Organisational Commitment in Primary School - Nazarudin, Mohamad Nizam; Omar Fauzee, Mohd Sofian; Abd Latif, Rozita (2008)
The study aimed to explore the level of headmaster’s transformational leadership/the level of teachers/organizational commitment and the relationship between headmaster’s leadership style and the organisational commitment of primary school teachers in Beaufort, Sabah, Malaysia. The model of transformational leadership developed by Bass (1985) and the organisational commitment model which was developed by Meyer and Allen (1991) served as the theoretical framework for the study. The transformational leadership classified into inspirational motivation intellectual stimulation and individual consideration. The organisational commitment on the other hand divided into affective commitment; continuance commitment and normative commitment. Data was obtained from 130 Beauforts, primary schools teachers. The research only dealt with Grade A schools. Two questionnaires were used as the main instrument; Alimo-Metcalfe’s (2001) Transformational Leadership Questionnaire (TLQ) which consisted of 21 items and Meyer and Aliens (1997) Organisational Commitment Questionnaire (OCQ)/ which consisted of 18 items. Data was analysed with SPSS for windows version 15.0. An average positive relationship between headmaster’s inspirational motivation and teacher’s organisational commitment was found. As perceived by the teachers/ the level of headmaster’s transformational leadership in Beaufort, was high in most schools. The research also indicated that the level of teacher’s organisational commitment was average. This research also suggested numbers of ways to improve teacher’s organisational commitment.